Pengaruh Self-Efficacy Dan Organizational Communication terhadap Employee Performance melalui Organizational Citizenship Behavior sebagai Variabel Intervening (Studi pada CV. Kalika Intergraha) - Puja Paramitha Devaya; Widiartanto Widiartanto; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2023)
The large amount of forest potential in Indonesia is an opportunity for entrepreneurs to establish a furniture industry, including CV. Kalika Intergraha which still survives. But in fact, the performance of CV. Kalika employees.has experienced fluctuations, especially in the performance of finishing employees for 4 years which continued to decline. This study aims to determine the influence of self-efficacy and organizational communication on employee performance through organizational citizenship behavior as an intervening variable, as well as organizational citizenship behavior. This type of research is explanatory research using a sample of 72 respondents who are permanent employees and finishing employees of CV. Kalika Intergraha. The results of this study indicate that each variable of self-efficacy and organizational communication has a positive and significant effect on employee performance through organizational citizenship behavior as a partial mediation.